Households' WTP for the reliability of gas supply - Wan-jung Chou; Andrea Bigano; Alistair Hunt; Stephane la Branche; Anil Markandya; Roberta Pierfederici (Fondazione Eni Enrico Mattei (FEEM), 2011)
The security of natural gas supply is an important issue for all EU countries due to the region's heavy dependence on imported supply sources and in light of energy demand for gas that is continuously increasing. Discussions have emphasised strategies for securing the supply at the macro level, e.g. diversification in supply sources, increase in storage capacity, etc. By contrast, consumers' demand for the reliability of gas supply is rarely investigated. Hence this study was conducted to examine the economic implications associated with the security of gas supply directly to domestic consumers. Based on the choice experiment approach, household surveys were conducted in France, Italy and the UK. The results confirmed that the degree of the economic impact of a disruption of gas supply to domestic consumers was a function of the duration of a supply disruption and the season in which a supply cut would take place, as well as other preferences of consumers. The willingness to pay to secure per unit of gas consumption, or alternatively the costs of gas unsupplied, was estimated at between exteuro2.65/cubic metre and exteuro41.48/cubic metre across three different European countries.
Keywords: C35; C83; C93; D12; Q41; 330; Energy Security; Gas Supply; Households; Willingness to Pay; Choice Experiment; EU